2012
DOI: 10.1007/s10531-012-0259-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-taxon congruence of α and β diversity among five leaf litter arthropod groups in Colombia

Abstract: In this study a and b diversity patterns of five leaf litter arthropod groups (ants, predatory ants, oribatid mites, spiders and other arachnids) were described and compared in 39 sampling patches of a transformed landscape in southwestern Colombia, that represented five vegetation types: secondary forest, riparian forest, giant bamboo forest, pasture and sugarcane crop. It was also assessed whether some taxa could be used as diversity surrogates. A total of 6,765 individuals grouped in 290 morphospecies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 59 publications
3
13
1
2
Order By: Relevance
“…However, this result is in line with other studies demonstrating higher cross-taxon concordance in b, rather than a-diversity (McKnight et al 2007;Kessler et al 2009; but see Cabra-Garcia et al 2012). This is partly explainable by the fact that a-diversity does not take into account information on taxonomic composition, in opposite to bdiversity.…”
Section: Fish and Macroinvertebratessupporting
confidence: 91%
“…However, this result is in line with other studies demonstrating higher cross-taxon concordance in b, rather than a-diversity (McKnight et al 2007;Kessler et al 2009; but see Cabra-Garcia et al 2012). This is partly explainable by the fact that a-diversity does not take into account information on taxonomic composition, in opposite to bdiversity.…”
Section: Fish and Macroinvertebratessupporting
confidence: 91%
“…In the present case, this is clearly supported by the difference between savanna and improved pastures on the one side, and rubber plantations and oil palm plantations on the other. Past research suggests that ecosystems with trees are more complex and offer a higher diversity of micro-habitats and niches, which could allow them to host a higher ant diversity [36]. However, in this study improved pastures showed the highest numbers of species followed by savannas, and they share 31 species in total [16].…”
Section: Effect Of the Regions Or Land Uses And Ant Or Termite Communcontrasting
confidence: 54%
“…The energy hypothesis, a climatically based hypothesis, claims that species richness within an area is limited by energy availability (Clarke & Gaston, 2006). These three hypotheses have received increasing support in explaining cross-taxon congruence in multiple terrestrial and marine taxa, including mammals, birds, insects, and vascular plants (Cabra-García, Bermúdez-Rivas, Osorio, & Chacón, 2012;Miranda & Parrini, 2015;Oertli et al, 2005). In contrast, the heterogeneity hypothesis states that species richness is higher in larger and more heterogeneous areas through increasing habitat availability and diversity (Whittaker et al, 2001).…”
Section: Introductionmentioning
confidence: 99%